Support of Maritime Education and Training Systems for the Implementation of the ISM Code - Elena Maggi; Marco Mazzarino (Promet (Zagreb), 2012)
The problem of the safety improvement and pollution preventionin maritime tra11Sp011 has become more and more criticaland urgent to solve. In fact, the number of accidents at seahas increased very quickly over time. Concern is growing aboutpoor qualification on safety and poor management standardsin shipping industry. The ISM Code (Intenzational Safety ManagementCode) aims to provide intemational standards for safemanagement of ship operations and for pollution prevention.The paper, which presents a part of the work done by the Universityof Trieste - ISTIEE within the framework of theMETHAR project, aims to identify the expected supp01t fromthe MaJitime Education and Training (MET) systems to implemmttheISM Code, consequently improving safety and preventingpollution. The paper desCiibes first the 01igin, the objectivesof the ISM Code and the standard requirements on METidentified by the Code. Secondly, it summarises the opinions ofthe operators collected through questionnaires. Finally, it identifiesthe possible enrichment of the MET system in order tobel/.er optimise the implementation of the Code.